Balance sheet strength and bank lending during the global financial crisis - Tümer Kapan; Camelia Minoiu (Deutsche Bundesbank, 2013)
We examine the role of bank balance sheet strength in the transmission of financial sector shocks to the real economy. Using data from the syndicated loan market, we exploit variation in banks' reliance on wholesale funding and their structural liquidity positions in 2007Q2 to estimate the impact of exposure to market freezes during 2007-08 on the supply of bank credit. We find that banks with strong balance sheets were better able to maintain lending during the crisis. In particular, banks that were ex ante more dependent on market funding and had lower structural liquidity reduced the supply of credit more than other banks. However, higher levels of better-quality capital mitigated this effect. Our results suggest that strong bank balance sheets are key for the recovery of credit following crises, and provide support for regulatory proposals under the Basel III framework.
Keywords: G21; G18; G01; 330; bank lending channel; wholesale funding; capital; net stable funding ratio; Basel III